PENINGKATAN KEMAMPUAN LITERASI DAN NUMERASI MELALUI PROGRAM KAMPUS MENGAJAR PADA SISWA DI SMP SWASTA ADVENT 5 MEDAN - Elfira, Eqlima; Syaufani, Akhmad; Pranata, Teo; Simanullang, Nopry Hiskia Hamonangan; Leonardo, Roy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The numeracy literacy skills of students in Indonesia are still lacking or quite low and still need to be improved. This is due to the influence of inappropriate technology adaptation. The purpose of this activity is to implement several teaching campus programs that will improve the literacy and numeracy skills of Advent 5 Medan Private Junior High School students. This activity was carried out from February to June 2024. The methods used in this activity are lectures, discussions and direct practice in front of the class. At the end of the activity, students will be given a quiz activity to hone their thinking skills in answering literacy and numeracy questions. This activity also provides benefits for students in exploring talents and interests in critical thinking to solve literacy and numeracy problems in students. The result of this activity is that students are able to carry out several activities such as, reading, writing, counting, and competing quickly in answering literacy and numeracy questions. The benefits of this activity also provide very high motivation in exploring students' cognitive, psychomotor and motoric abilities in personal branding to become students with superior and competitive character.